Agronomic performance and economic viability of maize cultivars of open pollination - Rossato, Rovani Marcos; Follmann, Diego Nicolau; Santos, Maurício Siqueira dos; Stefanello, Pedro Casarotto; Rodrigues, João Pedro Morais Fagundes (Scientia Agraria Paranaensis, 2021)
The open pollination cultivars (VPA) of maize are an alternative of production for a small property, because it presents a good agronomic performance and low production cost, mainly due to the possibility of seed production with low cost. The objective of this research was to evaluate the agronomic performance and economic viability of open pollination cultivars of maize in a low-altitude site in the central region of the state of Rio Grande do Sul. The experiment was conducted during the 2018/2019 crop season, in the experimental area of the Federal University of Santa Maria-UFSM, in the municipality of Santa Maria-RS. The open pollination maize cultivars (SCS 154 Fortuna, SCS 155 Catarina, and SCS 156 Colorado) were used. The experiment consisted of three treatments and four replicates and the experimental design used was that of complete blocks at random. The open pollination cultivars presented an adequate agronomic performance in a low-altitude region in the state of Rio Grande do Sul, associated with the economic viability of the crop in the central region of the state.